Cosmopolitan paradox dynamic egalitarianism in the redevelopment of the Cultural Center of the Philippines complex - Morallos, Chris Jehram M. (College of Architecture, University of the Philippines Diliman, 2025)
The Cultural Center of the Philippines (CCP) Complex stands as a testament to Filipino cultural identity, yet it faces mounting challenges, including governance inefficiencies, commercialization, and physical decline. The non-implementation of the 2003 master plan and the persistence of the Edifice Complex have hindered its ability to evolve as an inclusive cultural space. This study critically examines how architectural monumentalism, centralized governance, and global-local tensions have shaped the complex's trajectory and explores strategies for its adaptive redevelopment. Employing a mixed-methods approach, including archival research, stakeholder interviews, surveys, and spatial assessments-this research evaluates the CCP's architectural, cultural, and institutional landscapes. Findings reveal that monumentalism and state-driven narratives have marginalized participatory governance, limiting the complex's engagement with contemporary cultural dynamics. In response, the study introduces Symbiotic Pluralism, a framework integrating UNESCO's Historic Urban Landscape (HUL) principles, participatory governance, and sustainable urban strategies. By reconciling heritage conservation with inclusive modernization, the CCP can reassert its role as a living cultural institution that bridges historical legacy and contemporary Filipino identity. This study underscores the imperative for responsive, community-driven policies to sustain the CCP as a dynamic, relevant, and accessible cultural hub.